Contemporary oligarchy: the government of few disguised as democracy (Papeles, 2018)
It has been sold us the idea of democracy as the government of the people, where the social interests are represented by a single person elected by the society itself. The present proyect pretends, among many others objectives, put into question this definition througth a deductive analysis of the polls made by our investigation group along the last months. In Colombia the act of not voting has become a general action since the half of the last century until today, and although democracy is not just voting, this exercise is a general feature in democratic societies and a categorical factor in knowing the will of the majority. Our final purpose is that to the end of this work the reader may question if the abstentionism phenomenon corresponds to a lack of credibility in democracy, to the desinterest and desinformation of the people, or both.
Keywords: abstentionism; democracy; elections; Colombia; government; social interests; information